Galectin isolated from parasite inhibits remission of experimental autoimmune encephalomyelitis by up‐regulating autoantibody. (15th May 2015) - Bing, S. J.; Ha, D.; Ahn, G.; Cho, J.; Kim, A.; Park, S. K.; Yu, H. S.; Jee, Y.
Summary Recently, parasite infections or parasite‐derived products have been suggested as a therapeutic strategy with suppression of immunopathology, which involves the induction of regulatory T cells or/and T helper type 2 (Th2) responses. In a recent study, researchers reported that constructed recombinant galectin (rTl‐gal) isolated from an adult worm of the gastrointestinal nematode parasite Toxascaris leonina attenuated clinical symptoms of inflammatory bowel disease in mice treated with dextran sulphate sodium. Noting the role of rTl‐gal in inflammatory disease, we attempted to investigate the effect of the parasite via its rTl‐gal on neuronal autoimmune disease using experimental autoimmune encephalomyelitis (EAE), a mouse inflammatory and demyelinating autoimmune disease model of human multiple sclerosis. In this model, rTl‐gal‐treated experimental autoimmune encephalomyelitis (EAE) mice failed to recover after the peak of the disease, leading to persistent central nervous system (CNS) damage, such as demyelination, gliosis and axonal damage. Further, rTl‐gal‐treated EAE mice markedly increased the number of CD45R/B220+ B cells in both infiltrated inflammation and the periphery, along with the increased production of autoantibody [anti‐myelin oligodendrocyte glycoprotein (MOG)35–55] in serum at chronic stage. Upon antigen restimulation, rTl‐gal treatment affected the release of overall cytokines, especially interferon (IFN)‐γ and tumour necrosis factor (TNF)‐α. Our results suggest that galectin isolated from a gastrointestinal parasite can deliver a harmful effect to EAE contrary to its beneficial effect on inflammatory bowel disease.